The fabrication of artificial marble from dolomite (Batu Reput) - Kamarudin, Hussin; Shamsul Baharin, Jamaludin; Che Mohd Ruzaidi, Ghazali; Mohd Sobri, Idris; Mohd Nazry, Salleh; Mohabattul Zaman, S NS Bukhari; Khairul Nizar, Ismail (The Mineral, Metals & Materials Society (TMS), 2009)
Link to publisher's homepage at http://www.tms.org/TMSHome.aspx